PENERAPAN ASUHAN KEPERAWATAN PADA PASIEN Ny.Y DENGAN GAGAL GINJAL KRONIK (GGK) DALAM PEMENUHAN KEBUTUHAN CAIRAN DAN ELEKTROLIT DI RUANG HEMODIALISA RSUD LABUANG BAJI MAKASSAR - Nurlina Nurlina (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2018)
ABSTRACT Background: Based on data from the World Health Organization (WHO) showing that suffering from acute and chronic kidney failure is 50% while only 25% and 12.5% are treated and treated well. The cause of renal failure occurs when the kidneys are unable to transport the body's metabolic waste or perform its regular function, a substance that is normally eliminated in the urine accumulate in body fluids due to renal excretion and leads to impaired endocrine and metabolic functions, fluids, electrolytes, and acid-base acids. Objective: to give an idea of nursing care to Ny.